Впровадження гендерного підходу у процес підготовки майбутніх вчителів початкової школи - Самойленко, Неля; Samojlenko, N. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті виокремлено основні напрями досліджень по впровадженню гендерного підходу у процес підготовки майбутніх педагогів; визначено законодавчі акти, що регулюють питання професійної підготовки в контексті забезпечення ґендерної рівності; проаналізовано основні положення ґендерного підходу, розкрито специфіку його застосування у формуванні особистості майбутніх педагогів. Possibilities of development of all fields of the modern society require the implementation of the gender quality idea. Gender socialization process of young people is the most effective during professional training under conditions of educational aspects that influence on egalitarian consciousness of the students. Training of the future teachers according to implementation oh the gender quality approach in the professional activities is still topical nowadays. However there are the distinctive features: requirements of gender quality providing, state level support, conditions of the implementation, importance of providing the gender quality but impossibility of the implementation in modern conditions. This article emphasizes the main directions of the research of the gender quality implementation approach in the process of training the future teachers. We also have defined the legislative documents that control and regulate the issue of professional training of future teachers according to gender quality. We analyzed the most significant statements of the gender approach and researched the peculiarities of use this issue in the personal formation of the future teachers. Gender approach implementation in training process of future teachers of elementary schools.
Gender mainstreaming in the preparation of the future teacher of primary school.
Keywords: ґендер; gender; ґендерний підхід; майбутній педагог; початкова школа; вчитель; future teacher; gender mainstreaming; elementary schools; teacher